Immunomodulatory Effects of Probiotic Bacillus siamensis (ZMT02) on the Gross, Histomorphology and Histometric Indices of the Bursa of Fabricius in Broiler Chicken - Sundaramoorthy, Yamini; Selvan Paramadayalan, Senthamil; Kaliyaperumal, Rajalakshmi; Quintoil Mohanadasse, Nithya; Arasan, Varun; Mukul Ray, Susim (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Bursa of Fabricius is the primary lymphoid organ and is the source of B lymphocytes for humoral immunity against pathogens in birds. Probiotic feeding as an alternate to antibiotic use is gaining impetus. The present study reports the immunomodulatory effects of Bacillus siamensis (ZMT02) as a potential probiotic supplement Vs. Zinc bacitracin on the gross morphology, histomorphology and morphometric indices of the Bursa of Fabricius in broiler chicken that were challenged with pathogenic E. coli and Clostridium perfringens. At slaughter (42 days post feeding), the gross and histomorphological features of the bursa of Fabricius in control, antibiotic (Zinc bacitracin 500 mg/ton feed feed) supplemented and probiotic (Bacillus siamensis ZMT02, 1000 mg/ton) supplemented groups were normal without any abnormalities. Morphometric and volumetric measurements were comparatively larger and heavier in the control group and were smaller and lowest for the antibiotic group. There was no significant difference in the number of follicles between groups but the average follicular diameter was highest for the probiotic group with a distinct and well developed thicker cortex and was lowest for the antibiotic supplemented group with a thinner and poor cortex. Antibiotic supplementation had affected the proliferation and maturation of the B cells that resulted in smaller follicles with lean cortex. Probiotc supplementation with Bacillus siamensis was immunostimulatory and induced formation of larger follicles with a well developed cortex. The higher weight and volume of the bursa at slaughter in control birds might have resulted from the higher capillary network and repopulated immune cells after a transient immunodepletion.